PERENCANAAN TRAFFIC LIGHT PADA SIMPANG JALAN JENDERAL URIP SUMOHARJO – JALAN HOS COKROAMINOTO – JALAN JOHAR – JALAN MERDEKA KOTA PONTIANAK - Wirianata, Ade Dwija; AS, Syafaruddin; ., Sumiyattinah (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2016)
Intersection is the concourse of three or more roads or intersect on the urban road network system. In the high volume of traffic, especially at rush hour at the intersection of often conflicting traffic flows that can be dangerous for road users. This can be seen from the congestion that occurs on the streets and intersections protocol unresolved generally in Pontianak, particularly at the intersection of Jl. General Urip S. - Jl. HOS Cokroaminoto - Jl. Johar - Jl. Merdeka Although the police have to work extra hard regulate traffic, but traffic jams still occur. Based on this, the purpose of the writing of this study was to analyze and evaluate the existing condition of the crossing and arranging intersections into traffic light settings. So we get the planning traffic light at the intersection In writing this study researchers used survey methodology, namely to observe the conditions on the location of the intersection of Jl. JendralUrip S. - Jl. HOS Cokroaminoto - Jl. Johar - Jl. Freedom and collection of secondary data, traffic flow and non-motorized vehicles. Then compile the data that has been collected is processed by using theoretical calculations Indonesian Highway Capacity Manual (MKJI) 1997 quantitatively. Furthermore, the data that has been processed is the basis of researchers in preparing the plan of arrangement traffic lights that comply with the Indonesian Highway Capacity Manual (MKJI) 1997. Results from this study is the existing condition with diameter dimension span of the roundabout was not in accordance with the regulations MKJI 1997 and Guidelines for the Roundabout Intersection piece, which is 9 meters. And the threshold of traffic flow conditions on average per hour at the intersection that is> 750 veh / h, so it needs to re-planning to organize the intersection with the traffic light settings. From planning the traffic light settings in 2015, then obtained a green signal, namely Jl. Jend Urip Sumoharjo 13 sec, Jl. HOS Cokroaminoto 14 sec, Jl. Johar 26 sec and Jl. Merdeka 12 sec. For 2020 after analyzed. It turned out that the traffic light settings in 2015 can not be used anymore because it is based on current traffic conditions perpertumbuhan the degree of saturation (DS) to 1,363. Keywords: intersection, IHCM, traffic, traffic light